The Controversy of Democracy in Indonesia Presidential Election 2024 - Fernando, Henky; Larasati, Yuniar Galuh; Wuysang, Julia Magdalena; Cahyani, Novita; Hakim, Putri Rahmah Nur; Julkarnaen, Julkarnaen (Universitas of Muhammadiyah Makassar, 2024)
The presidential election in Indonesia in 2024 has raised controversy in the process and implementation of democracy. However, this context has not been comprehensively discussed in previous studies. In addition to answering the shortcomings of previous studies, this research also focuses on the question of how the forms, factors, and implications of democratic controversy on the legitimacy of presidential election results in Indonesia 2024. This research reveals three important findings related to democratic controversy in the 2024 presidential election in Indonesia. First, politicians’ and election organisers’ feeble commitment to complying with the rules of democratic elections. Second, the massive intervention of politicians and election organisers in the electoral process. Third, the controversy of democracy in the 2024 presidential election in Indonesia has long implications for citizens’ attitudes towards the legitimacy of election results. From these three contexts, it can be reflected that the democratic controversy in the 2024 Presidential Election in Indonesia not only caused democratic controversy in the electoral process and implementation, but also formed negative attitudes and perceptions of citizens towards the legitimacy of election results.